Implementation of green building maintenance in Malaysia: issues and challenges - Shiela Sharif; Syahrul Nizam Kamaruzzaman; Pitt, Michael; Farhan Ab Rahman (Penerbit Universiti Kebangsaan Malaysia, 2018)
The purpose of this paper is to highlight the issues and challenges in the Implementation of Green Building (GB) Maintenance in Malaysia. Addressing all the challenges and issues in Implementation of GB Maintenance in Malaysia efficiently and positively is very important to ensure the success of implementation and execution of the GB in Malaysia. Based on the literature, six (6) challenges have been identified as the major issues to the Implementation of GB Maintenance in Malaysia such as 1) difficult to justify and manage GB maintenance contract; 2) difficult to relate the GB maintenance and GB rating tools and assessment; 3) difficult to justify life-cycle cost and wear and tear period for GB features, equipment, and innovations; 4) skilful and knowledgeable GB maintenance contractor; 5) maintenance budget allocation vs. return of investment for long-term saving; and 6) managing the client, end-user and stakeholder’s awareness about GB usage and maintenance. This paper hopes to initiate a new perspective in the smooth and effective implementation of GB Projects in Malaysia by mitigating the challenges and issues in implementing it.